Low-cost culture medium for biomass production of lactic acid bacteria with probiotic potential destined to broilers = Desarrollo de un medio de cultivo de bajo costo para la producción de biomasa potencialmente probiótica destinado a pollos parrilleros - Berisvil, Ayelén Patricia; Astesana, Diego Martín; Zimmermann, Jorge Alberto; Frizzo, Laureano Sebastian; Rossler, Eugenia; Romero Scharpen, Analía; Olivero, Carolina Raquel; Zbrun, María Virginia; Signorini Porchiett, Marcelo Lisandro; Sequeira, Gabriel Jorge; Drago, Silvina; Soto, Lorena Paola (Facultad de Ciencias Veterinarias, Universidad Nacional del Litoral, 2021)
The aim of this study was to evaluate different low-cost culture media for biomass production of 3 potential probiotic L. salivariusstrains, which could be destined to broilers at farms. Different formulated media based on whey permeate (WP) supplemented with nitrogenous sources were evaluated: yeast extract (YE), whey hydrolysate (WH) and MnSO4.H2O (Mn), MgSO4.7H2O (Mg). The growth of each strain in the formulated media and the cost was compared with their growth and cost in commercial medium (MRS). L. salivarius DSPV008P did not grow adequately in any of the formulated media. On the other hand, addition of YE and Mn in the formulated media increased L. salivarius DSPV002P and L. salivarius DPSV011P growth. In contrast, WH and Mg addition increased the L. salivarius DSPV002P biomass only. L. salivarius DSPV011P was the only strain that had similar growth performance in MRS as in the selected medium: WP + YE 8g/l + Mn. In this sense, L. salivariusDSPV011P reached a biomass of 9.22 Log (CFU/ml) in the selected formulated medium, with a low-cost growth medium 12 times less than in MRS. Although the effect of supplements added to the culture medium on kinetic parameters are strain dependent, L. salivarius DSPV011P is the strain with the best technological characteristics, capable of growing in a medium based on a by-product of the dairy industry supplemented with YE and Mn and at a much less cost than in MRS medium.